‘Downtown mosaics’ in revitalisation district in Szczecin (Poland). Reflections on the project - Krawczak, Ada (Annales Universitatis Paedagogicae Cracoviensis. Studia de Arte et Educatione, 2022)
One of the most degraded areas of Szczecin is the city center with its three housing estates: Centrum, Śródmieście Zachud and Turzyn. The City Hall has been running a revitalisation program for this area since 2017. OSWAJANIE SZTUKI Association, which has been running the ŚRODEK Śródmiejski Punkt Sąsiedzki since 2018, located in the area covered by revitalisation, is implementing the artistic and social project ‘Downtown mosaics.’ The aim of the project is to create art objects in a degenerated semi-public space and to improve the attractiveness of places that the inhabitants of the area consider unattractive and/or dangerous. Mosaics are created in cooperation with local artists, urban activists and city residents in the courtyards of tenement quarters, outside the main walking trails. Designers present proposals for three mosaics, but the final choice is made by the residents of the nearest residential buildings or the direct owner of the facility. So far, five mosaics have been created on various topics – from ‘Cosmos’ behind the former Kosmos cinema to ‘Reading room’ on the garage wall of the owner of an informal antique shop. In addition to actively joining the mosaic, the residents can provide the material for the mosaic – e.g. tiles left over from home renovation. The mosaics became an attraction not only for the closest residents, but also met with a very positive reception from all Szczecin residents who began to visit the dark corners of the city center. The article presents the process of creating neighbourly mosaics in the spirit of participatory art.